2005
DOI: 10.3367/ufnr.0175.200507d.0745
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal martensitic transformations

Abstract: ¡ÐÂÎÑÅËÚÐÑÇ ÔÑÑÕÐÑÛÇÐËÇ ÐÇÒÑÔÓÇAEÔÕÄÇÐÐÑ ÔÎÇAEÖÇÕ Ë ËÊ ÎËÐÇÌÐÑÌ ÊÂÄËÔËÏÑÔÕË àÐÇÓÅËË ÂÍÕËÄÂÙËË ª®± Ä ÔÒÎÂÄÂØ Fe ë Ni ë Mn, ÒÑÎÖÚÇÐÐÑÌ Ä [103] (ÓËÔ. 13): Martensite transformations have long been considered most characteristically athermal ì in the sense that they develop, with changing temperature, at a tremendous temperature-independent rate and cease to occur at isothermal conditions. Over the past decades, however, isothermal martensite transformations (IMTs) have been discovered and studied, which take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…For example, it was observed that in the Fe-Ni alloys with concentrations of 20-28 wt.% of Ni martensite with a high dislocation density arises upon cooling, with the content 28-32 wt.% of Ni dislocations, and thin twins are observed in the martensite and, at a concentration of more than 32 wt.% Ni, martensite contains mainly twins [5]. It was shown that degree of the recovery in these alloys during change of substructure of the martensitic crystals from dislocations to twins increases from 10% (for Fe-20 wt.% Ni) to 35% (for Fe-32 wt.% Ni) (see Fig.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it was observed that in the Fe-Ni alloys with concentrations of 20-28 wt.% of Ni martensite with a high dislocation density arises upon cooling, with the content 28-32 wt.% of Ni dislocations, and thin twins are observed in the martensite and, at a concentration of more than 32 wt.% Ni, martensite contains mainly twins [5]. It was shown that degree of the recovery in these alloys during change of substructure of the martensitic crystals from dislocations to twins increases from 10% (for Fe-20 wt.% Ni) to 35% (for Fe-32 wt.% Ni) (see Fig.…”
Section: 2mentioning
confidence: 99%
“…However, in the case of isothermal martensitic transition, deformation caused by MT may occur at constant temperature without change of the applied stresses. For example, using alloys of Cu-Sn-Ga, in which isothermal kinetics of MT occurs, it was shown that accumulation of fully reversible deformation may occur at constant temperature in the temperature range [196C; 20C] and under constant applied stress during 20- 30 minutes [5,6]. When removing the applied stresses and heating above A f , there is complete recovery of the original state and size.…”
Section: Shape-memory Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…контактная температура, скорость нагрева, отпуск мартенсита, скорость диффузии, тем-пература аустенитизации into an austenitic structure, that is, an inverse martensitic transformation takes place. This transformation is all the more facilitated by the fact that as a result of the high specific pressures exerted by the abrasive grains on the surface of the metal, the Ac 1 point is shifted to a region of lower temperatures [2,4,5].…”
Section: A O V C H a R E N K Omentioning
confidence: 99%